The world at a glance - Tessema, Aster. 4 0 16; 5 (Dubuque, IA : McGraw-Hill, 2006)
Presents up-to-date data and accurate information about the nations of the world, covering details such as capitals, type of government, currency, major languages, population, religions, political structure, climate, and economics.
Adult;Adult
Keywords: 2 -- 0; 6; Geography.;Geography.; 20; 2